TEST OF REMOVAL OF IRON MINERALS FROM KAOLIN USING HGMS - Lili Tahli (Indonesian Mining Journal, 2008)
Kaolin from Nagreg contains iron mineral particles approximately 0.58 % Fe that cause a grey color of the material . An effort to reduce iron content can be made by applying beneficiation test, using HGMS (High Gradient Magnetic Separator), so the kaolin may become white color and can reach the standard quality for paper industries. A HGMS beneficiation test was conducted at magnetic field strength of 5,000 Gauss. The experi- ments were carried out using variable flow rates of 1, 1.5, 2, 2.5, 3 and 3.5 liter per minute and slurry density of 2.5, 5, 7.5, 10, 12.5 and 15 % solid. The results of experiments show that the optimum condition with flow rate of 2.5 liters/minute gave the quality of kaolin concentrate with iron content of 0.29 %Fe.